Analisis Adaptasi Sopir Angkutan Kota Konvensional Di Jakarta Dalam Menghadapi Dampak Kehadiran Mikrotrans Jak Lingko - Wildan Fido Ramadhan; Abdul Haris Fatgehipon; Nandi Kurniawan (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2024)
The presence of changes and improvements in transportation modes seems to bring a bad news for conventional city transportation drivers in Jakarta, because not all of them are able to adapt to these changes. The aim of this research is to determine the factors of conventional city transport drivers who persist with the conventional system and to determine the adaptation strategies carried out to survive after the presence of the Jak Lingko Microtrans. This research uses a descriptive method with a qualitative approach. Data collection techniques were carried out using interviews, Focus Group Discussions, and observations. The subjects in this research were conventional city transport drivers on the T.09 route Kalisari – Pasar Rebo. The research results show that conventional transport drivers still persist with the legal system due to: 1) Age factor, 2) Regulatory barriers, 3) Incentives, 4) Community needs, and 5) Distrust of operators. Then, the strategies used by city transport drivers are 1) active strategy by utilizing their own abilities, 2) passive by minimizing expenses, and 3) Networking by utilizing relationships and relatives. So it can be concluded that conventional transport drivers still persist with the conventional system due to several obstacles ranging from internal and external and in meeting their daily needs, these drivers use adaptation strategies as an alternative step amidst the problems they face.